IoT-enabled Assistive Gloves for Individuals with Disabilities - Alfiya Ayeesha N.; Neha Kumari V.; Suma P.; Varshini Rachana (International Journal of Algorithms Design and Analysis Review, 2023)
Every year, new technologies emerge, leaving varying degrees of impact on our daily lives, where some make a significant mark while others quickly fade into obscurity. Among the myriad of cutting-edge technologies, the Internet of Things (IoT) is particularly notable. In the present world, there are individuals who lack the ability to hear and speak, as well as those who face disabilities that hinder their social interactions. These individuals encounter substantial challenges when it comes to communication. So, with the advancement in technology there is an option for the disabled people to communicate with the help of sign language. But it would be difficult for normal people to understand. So, this paper describes the Smart Gloves to assist disabled, paralyzed and handicapped people which helps them to lead a normal life. Here in this model the flex sensors records the fingers motion, Ultrasonic sensor which is used to measure the distance of the object/obstacle at certain distance, a help button which is used in any emergency situations, ESP32 which is a microcontroller and a buzzer which rings when any object/obstacle is detected by the ultrasonic sensor also during the help switch is pressed, is basically used for alerting the surrounding people during emergency situations. All the data are also displayed in Android App for immediate attention.
Keywords: Assistive Gloves; Disabilities; ESP32; Flex sensors; ultrasonic sensors